2020
DOI: 10.1111/tpj.14897
|View full text |Cite|
|
Sign up to set email alerts
|

Arabidopsis plants expressing only the redox‐regulated Rca‐α isoform have constrained photosynthesis and plant growth

Abstract: SUMMARY Rubisco activase (Rca) facilitates the release of sugar‐phosphate inhibitors from the active sites of Rubisco and thereby plays a central role in initiating and sustaining Rubisco activation. In Arabidopsis, alternative splicing of a single Rca gene results in two Rca isoforms, Rca‐α and Rca‐β. Redox modulation of Rca‐α regulates the function of Rca‐α and Rca‐β acting together to control Rubisco activation. Although Arabidopsis Rca‐α alone less effectively activates Rubisco in vitro, it is not known ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The isothermal signal amplification technique is highly specific and requires low sample purity; if the sample does not contain the target sequence to be detected, the loop probe cannot be looped, and the amplification reaction will not occur [9]. The branched chain amplification effect can increase the sensitivity of detecting mutant molecules to about 10 copies, and its sensitivity is extremely high, and this technique is extremely advantageous in the identification of gonorrhea pathogens and the detection of drug resistance genes [10]. Therefore, the successful implementation of our study will definitely change the current status of gonorrhea diagnosis and treatment, and has excellent market demand and prospects.…”
Section: Introductionmentioning
confidence: 99%
“…The isothermal signal amplification technique is highly specific and requires low sample purity; if the sample does not contain the target sequence to be detected, the loop probe cannot be looped, and the amplification reaction will not occur [9]. The branched chain amplification effect can increase the sensitivity of detecting mutant molecules to about 10 copies, and its sensitivity is extremely high, and this technique is extremely advantageous in the identification of gonorrhea pathogens and the detection of drug resistance genes [10]. Therefore, the successful implementation of our study will definitely change the current status of gonorrhea diagnosis and treatment, and has excellent market demand and prospects.…”
Section: Introductionmentioning
confidence: 99%
“…Both GO enrichment and KEGG pathway analyses showed that photosynthesis‐related proteins are less abundant, indicating that these changes may reflect the different LUE under dynamic light conditions. Although stomatal movement and energy dissipation are important for effective utilization of dynamic light (Kromdijk et al, 2016; Yamori et al, 2020), the main factor limiting LUE under dynamic light conditions is generally believed to be the activity of the enzymes participating in CO 2 fixation (Acevedo‐Siaca et al, 2020, 2021; Kim et al, 2019, 2020; Salter et al, 2019; Soleh et al, 2017; Yamori et al, 2012). In particular, the activity of enzymes involved in CO 2 fixation are most likely to determine LUE when HL‐adapted leaves are exposed to dynamic light (Li et al, 2020).…”
Section: Resultsmentioning
confidence: 99%
“…The de-activation of the Rubisco and a reduced Pn have often been observed in long-term NaCl stress [29]. The mRNA levels of RBCS1A, which encodes a Rubisco small subunit that constitutes Rubisco [49], as well as RCA-A and RCA-B, which code for Rubisco activase responsible for activating Rubisco [50], and RPE and PRK were downregulated by saline in Hs. The transcript levels of these genes in Hs/Hh were significantly higher than those in Hs and Hs/Hh under salt conditions.…”
Section: Grafting Alleviates the Limitation Of Salt Stress On Photosy...mentioning
confidence: 99%